Готовность учителя к работе с детьми в гетерогенной образовательной среде: результаты опытно-экспериментального исследования - Smantser, Anatolij (Student Niepełnosprawny. Szkice i Rozprawy, 2019)
The article analyzes the theoretical aspects of training teachers for work in an inclusive environment, presents the results of a pilot experimental study of the effectiveness of the implementation of the main provisions of the "Concept of preparing trainees for the design of a psychologically safe heterogeneous educational environment".